(3OjhGf GHf CHj GdMOjOs - (3YHO GdMejO Hf gHI Gddg Hf eMeO Hf GdMSjf , GHf CHj GdMOjO , YR GdOjf CHh MGeO,J (B656 (3g` s ((3EHQGgje Hf ESeGYjd s)
(3ChdgG (B:s
(3CdG Ef fLO GdeLO CHjV edMhH hdcfg Le GdegGdc eQghH s
(3BNQgG (B:s
(3dOQ ef CdaGXg dcfg OQ dCHj GdMOjO jaUd dj Ohf eOM ajc hahb eG eOM GdhQi, hYdGc efgG Cced s
(3Vef eLehY s
(3HChd GdfSNI JQLeI dGHf CHj GdMOjOs
(3hHBNQgG CHjGJ efbhdI ef GdYbO GdaQjO ef cdGe GHf GHj GdMOjO eY TQM dHYV CdaGXgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B106 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B507s
Keywords: (3GdCOHs